Effective clearance of GL‐3 in a human iPSC‐derived cardiomyocyte model of Fabry disease. Issue 6 (22nd May 2014) - Itier, Jean‐Michel; Ret, Gwénaëlle; Viale, Sandra; Sweet, Lindsay; Bangari, Dinesh; Caron, Anne; Le‐Gall, Françoise; Bénichou, Bernard; Leonard, John; Deleuze, Jean‐François; Orsini, Cécile
Abstract: Fabry disease, a rare X‐linked α‐galactosidase A deficiency, causes progressive lysosomal accumulation of globotriaosylceramide (GL‐3) in a variety of cell types. As the disease progresses, renal failure, left ventricular hypertrophy, and strokes may occur. Enzyme replacement therapy (ERT), with recombinant α‐galactosidase A, is currently available for use to reduce GL‐3 deposits. However, although it improves cardiac function and decreases left ventricular mass, GL‐3 clearance upon ERT has been demonstrated in cardiac capillary endothelium but not in cardiomyocytes of patients. Relevant models are needed to understand the pathogenesis of cardiac disease and explore new therapeutic approaches. We generated induced pluripotent stem cells (iPSC) from Fabry patients and differentiated them into cardiomyocytes. In these cells, GL‐3 accumulates in the lysosomes over time, resulting in phenotypic changes similar to those found in cardiac tissue from Fabry patients. Using this human in vitro model, we demonstrated that substrate reduction therapy via glucosylceramide synthase inhibition was able to prevent accumulation and to clear lysosomal GL‐3 in cardiomyocytes. This new in vitro model recapitulates essential features of cardiomyocytes from patients with Fabry disease and therefore provides a useful and relevant tool for further investigations of new therapy.